World population projections, 2020 - Nygaard, David F. (International Food Policy Research Institute, 1994)
The world's population, today numbering some 5.5 billion people, may approach 12 billion by the end of the next century. By the year 2020, 26 years from today, it will most likely have increased by about 2.5 billion to a total of 8 billion people, an increase of nearly 100 million a year. Over 93 percent of this growth will take place in the developing countries. Nygaard contends that two regions in particular merit attention. South Asia and Africa, where large percentages of the poor live today and where future food production is of concern, face substantial increases in their populations. India, Pakistan, and Bangladesh plus the continent of Africa will add another 1.5 billion people to the population roles.